LONGITUDINAL EVALUATION OF THE EFFECTS OF POSTTRAUMATIC STRESS AFTER AN INDUSTRIAL CATASTROPHE. THE CASE OF SAN JUAN IXHUATEPEC COMMUNITY (MÉXICO) - Sigales Ruiz, Silvia Rosa (Anales de Psicología / Annals of Psychology, 2006)
This study identifies the posttraumatic effects caused by several industrial catastrophe occurred in the north of Mexico city between 1984 and 1996. A sample of 117 victims was assessed whit the ALFEST Scale (Steinitz y Crocq, 1992) to identify the effects of industrial accidents repetition (gas leakage from a petrochemical company: PEMEX, Petróleos Nexicanos). The results shown that a catastrophe of this kind causes significant posttraumatic effects on the mental health of the individuals along many years, and triggering specific psychotraumatic syndromes.